2021
DOI: 10.4081/jbr.2021.9680
|View full text |Cite
|
Sign up to set email alerts
|

Total phenolic and flavonoids contents and <i>in vitro</i> evaluation of antioxidant activity of several <i>Calendula officinalis</i> (Marigold) extracts

Abstract: The search for natural antioxidants to replace synthetic antioxidants is one of humanity’s health priorities. Medicinal and Aromatic Plants (MAP) contain phenolic compounds that act as natural antioxidants. The aim of this work is to study total phenols and flavonoids contents and evaluate the antioxidant power of various extracts of Calendula officinalis. Extracts were prepared in two steps: hot solid-liquid extraction, by Soxhlet and from the plant powder using a solvent (Methanol/water 70/30, Acetone/water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In epidemiological studies, fruits and vegetables in the diet have proven to protect against various chronic illnesses including cancer, cardiovascular disease, cataracts, and immunological dysfunction (Figure 8) [6,30]. Various phenolic and flavonoid constituents have been linked with natural protective benefits [31][32][33]. The biological actions of phenolics, which are powerful antioxidants and free radical scavengers, have been subject to several earlier investigations [34,35,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In epidemiological studies, fruits and vegetables in the diet have proven to protect against various chronic illnesses including cancer, cardiovascular disease, cataracts, and immunological dysfunction (Figure 8) [6,30]. Various phenolic and flavonoid constituents have been linked with natural protective benefits [31][32][33]. The biological actions of phenolics, which are powerful antioxidants and free radical scavengers, have been subject to several earlier investigations [34,35,28].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, polyphenols protect against human diseases associated with oxidative stress, like coronary heart disease and cancer [28,31]. After studying the literature, it was found that major polyphenolic classes which have prominent effects as antioxidants, and other health benefits present in Alstonia scholaris, Tabernaemontana divaricata, Tagetes erecta [8,13,18,33]. Antioxidant activity evaluation revealed that Saraca asoca showed great antioxidant activity in eliminating hydroxyl radicals (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Among the interesting properties of essential oils, the antioxidant and antibacterial activities are highly appreciated since they might help to address two significant issues affecting human health, namely oxidative stress and antibiotic resistance [6]. In fact, they can act as natural antioxidants and antibiotics and substitute the synthetic ones that might be noxious and unhealthy [7]. The essential oils of plants are a complex combination of chemical components.…”
Section: Introductionmentioning
confidence: 99%
“…Among the species of this family, the genus Origanum and Thymus are widely known and highly appreciated in traditional medicine throughout the world. In Morocco, both the species are included in the most significant medicinal plants commonly used in traditional medicine and mostly studied for their several biological activities [7,10,11]. Known locally as "Zaâtre" for O. compactum and "Zaîtra" for T. zygis, they may be applied against a wide spectrum of pathologies and in industrial fields such as foods, pharmaceuticals, aromatherapy and perfumes [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Various plant sections, such as leaves and flowers, have been stated to have therapeutic properties (3). The "Food and Drug Administration" (FDA) and t h e " F l a v o r s a n d E x t r a c t s M a n u f a c t u r e r s Association" (FEMA) have determined that the plant's components and dried flowers which are often used as spices are safe (4). According to the literature, C.officinalis has been widely studied for its various health benefits.…”
Section: Introductionmentioning
confidence: 99%